2021
DOI: 10.1111/cas.15118
|View full text |Cite
|
Sign up to set email alerts
|

C644‐0303, a small‐molecule inhibitor of the Wnt/β‐catenin pathway, suppresses colorectal cancer growth

Abstract: The Wnt/β‐catenin signaling pathway plays an important role in tissue homeostasis, and its malignant activation is closely related to the occurrence and development of many cancers, especially colorectal cancer with adenomatous polyposis coli (APC) and CTNNB1 mutations. By applying a TCF/lymphoid‐enhancing factor (LEF) luciferase reporter system, the high‐throughput screening of 18 840 small‐molecule compounds was performed. A novel scaffold compound, C644‐0303, was identified as a Wnt/β‐catenin signaling inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 76 publications
1
2
0
Order By: Relevance
“… 25 Inhibition of Wnt/β-catenin pathway through C644-0303 also impedes the growth of colorectal cancer. 26 In the current study, the expression levels of β-catenin, c-myc and MMP-7 were notably diminished in both AGS and MKN45 cells with transfection of shRAD54B and notably increased in both AGS and MKN45 cells transfected with RAD54B over-expression plasmid, which also confirmed in vivo . However, the contrary results were obtained in the relative protein expression of Axin in both AGS and MKN45 cells.…”
Section: Discussionsupporting
confidence: 81%
“… 25 Inhibition of Wnt/β-catenin pathway through C644-0303 also impedes the growth of colorectal cancer. 26 In the current study, the expression levels of β-catenin, c-myc and MMP-7 were notably diminished in both AGS and MKN45 cells with transfection of shRAD54B and notably increased in both AGS and MKN45 cells transfected with RAD54B over-expression plasmid, which also confirmed in vivo . However, the contrary results were obtained in the relative protein expression of Axin in both AGS and MKN45 cells.…”
Section: Discussionsupporting
confidence: 81%
“…Because HCT116 cells have detectable levels of HIF and WNT under a steady state and also respond to additional stimulus treatment, this allows us to study all interested characteristics in the same cell under both resting and stimulatory states. Although no anticancer HIF and WNT inhibitors are clinically available, some small-molecule inhibitors specific for HIF ( 46 ) or WNT ( 47 ) signaling exhibit sound HCT116 cell growth inhibition activity. Therefore, HIF1α and WNT luciferase reporter systems were developed in the HCT116 cells through multiple steps, which resulted in generating constructs that consisted of the luciferase reporter gene under the transcriptional regulation of an enhancer containing hypoxia-responsive element (HRE) or β-catenin–binding cis element (TCF/LEF1) upstream of a mini-TATA promoter, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, it has been suggested that shikonin-induced glycolysis (including the reduction of glucose 6-phosphate and pyruvate and the down-regulation of HK2 and PKM2) can be affected by RIP1 or RIP3 ( 186 ). PFKFB3 inhibitors can regulate the interaction of RIP1, RIP3 and MLKL, and induce necrotic apoptosis ( 187 ). There is a similar process of glycolysis during osteoarthritis as described above, and therefore intervention in necroptosis can rely on glycolytic interference.…”
Section: The Regulated Programmed Cell Death and Glycolysismentioning
confidence: 99%